Analysis of a Fractional-Order Nonlinear System with Hysteresis Nonlinearity via Describing Function - Barbosa, Ramiro S.; Jesus, Isabel S.; Machado, J.A. Tenreiro (Journal of Applied Nonlinear Dynamics, 2026)
The describing function(DF) is one method often used for the analysis of nonlinear systems and the prediction of limit-cycles. In this study, we explore the DF using frequency response methods in order to analyze the effectiveness of this technique in a fractional-order nonlinear system. Since it is common to find different types of nonlinearities in real systems, the DF method may reveal of great practical interest. In this perspective, we investigate the limit-cycle prediction and frequency response analysis of a fractional-orderplant model with hysteresis nonlinearity. The results presented may give some guidelines for the design of linear and nonlinear controllers of arbitrary order